2014
DOI: 10.3109/11038128.2013.870225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating intervention using time aids in children with disabilities

Abstract: This study provides preliminary evidence that time-processing ability and managing one's time can be improved by intervention using time aids in children with intellectual and developmental disabilities, supporting the need to consider time aids in intervention in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(84 citation statements)
references
References 37 publications
8
71
1
4
Order By: Relevance
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%
“…Reason for exclusion Barnett et al [86] Participants are teachers Benyakorn et al [87] Not interventional Bishop [88] Intervention not technology Bonarini et al [89] Population focus not ADHD Bul et al [90] Outcome measures do not assess ADHD-related difficulties Chan et al [91] Not interventional Chen et al [92] Not interventional Christiansen et al [93] Intervention reliant on others Dale and Grut [94] Not exclusively for ADHD Duffy [95] Population focus not ADHD Enebrink et al [96] Population focus not ADHD References Reason for exclusion Epstein et al [97] Intervention reliant on health care professionals Fiellin et al [98] Population focus not ADHD Frutos-Pascual et al [99] Population focus not ADHD Frutos-Pascual and GarciaZapirain [100] Participants typically developing, not ADHD Gray et al [72] ADHD not primary diagnosis of participants Halperin et al [101] Intervention not technology Janeslätt et al [102] Intervention not technology Kim et al [103] Intervention not technology Lim et al [104] Intervention reliant on health care professionals Mazurek and Engelhardt [105] Not interventional Myers et al [106] Participants ADHD diagnosis not confirmed Nie et al [107] Intervention not technology Pandria et al [108] Not interventional Rohani et al [109] Participants ADHD diagnosis not confirmed Rosch and Mostofsky [110] Not interventional Schafer et al [111] Participants not received ADHD diagnosis Schuck et al [112] Participants not received ADHD diagnosis Shah et al 2012 Not interventional Silva et al [113] Technology as outcome measure, not intervention Steeger et al 2016 Participants ADHD diagnosis not confirmed Stephenson [114] Population focus not ADHD Tse et al …”
Section: Appendix 2: References and Reasons For Exclusionmentioning
confidence: 99%
“…There is evidence for the effectiveness of assistive devices that compensate for a lack of time management in adults with developmental disabilities (e.g., IDs) (Arvidsson & Jonsson; Gillespie, Best & O'Neill, ; Granlund, Bond, Lindstöm & Wennberg, ; Wennberg & Kjellberg, ). A randomised controlled trial (RCT) provided preliminary evidence that TPA can improve in children with developmental disabilities as a consequence of using TADs (Janeslätt, Kottorp & Granlund, ). The study also underscores the need to develop methods that include remediation to complement interventions using TADs.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential explanation may be that the children with ID might have had access to time-assistive devices, to compensate for deficits in TPA. Since in Scandinavia persons with ID are the target group who have had access to time-assistive devices for the longest, especially low-tech products such as adapted weekly schedules and/or activity schedules (36,(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…They also had a weaker time reproduction than children without disabilities. It has been shown that children and adults with ID benefit from time-assistive devices to enhance DTM and TPA (35)(36)(37)(38) and that they can improve their TPA by training in low levels of TPA that focuses on time perception and the duration of activities (39).…”
Section: Children With Id and Difficulties With Timementioning
confidence: 99%
See 1 more Smart Citation